Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Kedai Warsu Coffe Cafe - Umami, Risatul; Rizal, As'at; Sumartik, Sumartik (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2019)
This research finds out the effect of product, price and service quality toward customer satisfaction both partially and simultaneously at Warsu Coffe Cafe. It is descriptive research with a quantitative method. The data were collected using questionnaires and documentation. The populations were the consumers who visited and bought a product in Warsu Coffe Cafe. The samples were 87 respondents that were chosen by using nonprobability sampling technique with incidental sampling type. The analysis technique used multiple linear regression. The result showed that both partially and simultaneously, the product, price, and service quality affect customer satisfaction. The most dominant influence is product quality on customer satisfaction, it shows that the Warsu Coffee Cafe has good product quality.